Structural Transformation of the Turkish Economy under the Scope of Sustainable Development - Karaalp-Orhana, Hacer Simay (European Journal of Sustainable Development, 2019)
The distribution of the labour force by sectors and the country economic structure indicate the economic development level of countries. The traditional sectoral transformation is observed in all countries during the economic development process. Since the establishment of the Republic of Turkey, industrialization has been one of the fundamental development policies to be achieved. As an inevitable result of the development, the sectoral distribution of production and employment changed in Turkish economy over the years. This structural transformation is associated with the transition from primary sector to capital intensive production structure in which the manufacturing and the service sectors expand while the agricultural sector shrinks. However, the agricultural sector is still important in Turkey. Today, approximately one-fifth of the labour force is employed in the agricultural sector. This ratio shows the developing country feature of Turkish labour market despite the industrialization and urbanization policies and the structural changes in recent years. In this context, the aim of this study is to analyze the sectoral transformation of the Turkish economy within the scope of the sectors share in the GDP of Turkey and the share of sectors in the total employment, within the changing structure of the labour market and the level of urbanization. Keywords: economic development, structural transformation, Turkish economy